2004
DOI: 10.1074/jbc.m400037200
|View full text |Cite
|
Sign up to set email alerts
|

As(III) and Sb(III) Uptake by GlpF and Efflux by ArsB in Escherichia coli

Abstract: The toxicity of the metalloids arsenic and antimony is related to uptake, whereas detoxification requires efflux. In this report we show that uptake of the trivalent inorganic forms of arsenic and antimony into cells of Escherichia coli is facilitated by the aquaglyceroporin channel GlpF and that transport of Sb(III) is catalyzed by the ArsB carrier protein; everted membrane vesicles accumulated Sb(III) with energy supplied by NADH oxidation, reflecting efflux from intact cells. Dissipation of either the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
164
1
17

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 260 publications
(186 citation statements)
references
References 23 publications
4
164
1
17
Order By: Relevance
“…However, in paddy soils, which are flooded during much of the rice growing season, arsenite becomes the predominant chemical species of As (14). It has been shown that arsenite is taken up via aquaglyceroporins in microbes (13,(15)(16)(17). Evidence from physiological studies suggests that arsenite may also be transported by aquaporins in rice (18), although the exact mechanism of arsenite uptake has not been identified in higher plants.…”
mentioning
confidence: 99%
“…However, in paddy soils, which are flooded during much of the rice growing season, arsenite becomes the predominant chemical species of As (14). It has been shown that arsenite is taken up via aquaglyceroporins in microbes (13,(15)(16)(17). Evidence from physiological studies suggests that arsenite may also be transported by aquaporins in rice (18), although the exact mechanism of arsenite uptake has not been identified in higher plants.…”
mentioning
confidence: 99%
“…It transports As(III) but has higher affinity for Sb(III). ArsB is an antiporter that catalyzes the exchange of trivalent metalloid for protons, coupling arsenite efflux to the electrochemical proton gradient (9).…”
mentioning
confidence: 99%
“…The ArsA subunit is an As(III)/Sb(III)-stimulated ATPase (21), and the ArsB subunit is an antiporter that catalyzes As(III)/H ϩ exchange (22). The 583-residue ArsA ATPase is composed of two homologous A1 and A2 halves that are connected by a short linker (3).…”
Section: Discussionmentioning
confidence: 99%